Childhood socioeconomic position and adult mental wellbeing: Evidence from four British birth cohort studies - Wood, Natasha (PLoS One, 2017)
BACKGROUND: There is much evidence showing that childhood socioeconomic position is associated with physical health in adulthood; however existing evidence on how early life disadvantage is associated with adult mental wellbeing is inconsistent. This paper investigated whether childhood socioeconomic position (SEP) is associated with adult mental wellbeing and to what extent any association is explained by adult SEP using harmonised data from four British birth cohort studies. METHODS: The sample comprised 20,717 participants with mental wellbeing data in the Hertfordshire Cohort Study (HCS), the MRC National Survey of Health and Development (NSHD), the National Child Development Study (NCDS), and the British Cohort Study (BCS70). Warwick Edinburgh Mental Wellbeing Scale (WEMWBS) scores at age 73 (HCS), 60–64 (NSHD), 50 (NCDS), or 42 (BCS70) were used. Harmonised socioeconomic position (Registrar General’s Social Classification) was ascertained in childhood (age 10/11) and adulthood (age 42/43). Associations between childhood SEP, adult SEP, and wellbeing were tested using linear regression and multi-group structural equation models. RESULTS: More advantaged father’s social class was associated with better adult mental wellbeing in the BCS70 and the NCDS. This association was independent of adult SEP in the BCS70 but fully mediated by adult SEP in the NCDS. There was no evidence of an association between father’s social class and adult mental wellbeing in the HCS or the NSHD. CONCLUSIONS: Socioeconomic conditions in childhood are directly and indirectly, through adult socioeconomic pathways, associated with adult mental wellbeing, but findings from these harmonised data suggest this association may depend on cohort or age.